Cardiotoxicity of 5-flourouracil: two case reports - (:unkn) unknown (ELSEVIER SCI LTD, 2001)
Cardiotoxicity is a ran but serious side effect of 5-flourouracil (5-FU), The cardiotoxicity incidence of 5-FU is increasing with its frequent use in chemotherapy protocols. To explain the mechanism of this cardiotoxicity, many theories have been suggested by different authors. Most commonly, coronary artery vasospasm and flouroacetate, a toxic metabolite of 5-FU, are considered responsible for the toxicity. Ischemic symptoms and signs related to 5-FU are observed during the late phase of the administration of the drug. The close and careful monitorization of all the patients, especially the ones with pre-existent coronary artery disease, during 5-FU infusion is mandatory. Because there is not a single and effective modality of treatment or prophylaxis for 5-FU cardiotoxicity. the patients should be selected carefully for 5-FU administration and 5-FU infusion should be stopped as soon as a symptom is encountered, (C) 2001 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: cardiotoxicity; 5-flourouracil; chemotherapy; 5-FLUOROURACIL CARDIOTOXICITY